Effects of Physical Activity, Fruit and Vegetables Intake, and Alcohol Consumption on Overweight or Obesity: Meta-Analysis - Solehaini, Dena Tri; Murti, Bhisma; Ichsan, Burhannudin (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Overweight or obesity is a public health problem worldwide which is increasing both in the general population and in people with chronic diseases. Overall both children and adults are vulnerable to overweight or obesity. This study aims to examine the effect of physical activity, consumption of vegetables and alcohol on overweight or obesity using a meta-analysis.Subjects and Method: Meta-analysis was carried out using the PRISMA flowchart and the PICO model. Population: age 6 to 64 years. Intervention: low physical activity, low vegetable and fruit consumption, and high alcohol. Comparison: high physical activity, high vegetable and fruit consumption, and alcohol low. Outcome: overweight or obese. The databases used are Google Scholar, PubMed, and Proquest with keywords (Overweight OR Obesity OR